A Review on the Hazardous Materials Removal Using Activated Carbons Derived from Walnut (Juglans regia L.) Shell - A. Jahanban-Esfahlan; R. Jahanban-Esfahlan; M. Tabibiazar; L. Roufegarinejad; R. Amarowicz (Iranian Journal of Chemical Engineering)
The shell of walnut fruit is an agricultural byproduct generated in considerable amounts upon the processing of fruit to obtain its valuable kernel. Walnut is recognized as an appreciated tree nut belonging to the Juglandaceae family. The fruit is mainly composed of a kernel, seed coat, shell, and husk. In recent years, the shell portion of walnut fruit has been widely used in the development of different high–value materials. In this regard, high carbon and low ash contents of the walnut shell (WS) make it a suitable material and inexpensive waste agricultural product for the activated carbon (AC) preparation. In this review, recent developments in the preparation of AC from the shell of walnut fruit and the characterization methods are highlighted. Additionally, the applications of AC mainly in the removal of different hazardous materials such as heavy metals (HMs) ions, dyes as well as pharmaceuticals and other dangerous materials are comprehensively discussed.